2022
DOI: 10.1021/acs.chemrev.2c00118
|View full text |Cite
|
Sign up to set email alerts
|

The Astounding World of Glycans from Giant Viruses

Abstract: Viruses are a heterogeneous ensemble of entities, all sharing the need for a suitable host to replicate. They are extremely diverse, varying in morphology, size, nature, and complexity of their genomic content. Typically, viruses use host-encoded glycosyltransferases and glycosidases to add and remove sugar residues from their glycoproteins. Thus, the structure of the glycans on the viral proteins have, to date, typically been considered to mimick those of the host. However, the more recently discovered large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 255 publications
0
19
0
Order By: Relevance
“…Interestingly, the same GMC-oxidoreductases also compose the surface fibrils of the virions (4,9,17). However, despite their involvement in both the mimivirus genomic fiber structures and the virion surface layer, homologs of these proteins are puzzlingly absent in the laboratory evolved mutant (strain M4) (17), suggesting they may not be essential.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the same GMC-oxidoreductases also compose the surface fibrils of the virions (4,9,17). However, despite their involvement in both the mimivirus genomic fiber structures and the virion surface layer, homologs of these proteins are puzzlingly absent in the laboratory evolved mutant (strain M4) (17), suggesting they may not be essential.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we aimed to determine whether GciS was conserved within Megavirinae, a proposed subfamily of Mimiviridae. 17 A simple blast search without filtering revealed that the protein was conserved in all members of clade A (mimivirus). Bioinformatic analyses also showed that orthologues of GciS from mimivirus may be found in other members of the subfamily.…”
mentioning
confidence: 99%
“…Giant viruses are nucleocytoplasmic large DNA viruses (NCLDVs) with up to 2.8 Mb genomes encoding 1500 proteins, most of them without resemblance to other cellular or viral proteins (ORFans). , Giant viruses are found in diverse habitats and infect eukaryotes, mostly protists and microalgae (reviewed in ref ). The first giant virus, mimivirus, was discovered in 2003.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins are biopolymers that exist broadly in living organisms, playing a wide range of pivotal roles in cell growth, differentiation, movement, catalyzing reactions, and more . Despite the 20 natural l -form amino acids, cells use more than 400 modifications, namely, post-translational modifications (PTMs), to accommodate environmental change, including phosphorating, acetylation, , glycosylation, , ubiquitylation, lipidation, , and beyond. In addition, chemical modifications targeting amino acid residues with high selectivity have also been developed in the past several decades, complementing natural modifications catalyzed by varied enzymes. , The lysine, cysteine, tyrosine, , arginine, histidine, methionine, , and tryptophan have been comprehensively investigated, and a wide range of reagents with highly selective manners have been explored (Figure A) .…”
mentioning
confidence: 99%